Quality of Service to Customer Satisfaction at Cafe Kofi Sawangan Depok - Amelia Azura Diva; Benny Osta Nababan; Septa Riadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to analyze the quality of service available at the cafe Kofi Sawangan Depok, to determine the value of the consumer satisfaction index at the Cafe Kofi Sawangan Depok and to determine the indicators that must be improved so that customer satisfaction can be met. This research uses descriptive method with quantitative data, the reason is because this research was conducted by collecting data in the form of numbers or sentences and then converted into analysis to obtain information. The population in the study were visitors to Cafe Kofi Sawangan Depok with a total sample of 100 respondents and was determined based on the Slovin formula. Data collection techniques were carried out using surveys and questionnaires, while for data analysis using Microsoft Excel 2010 and SPSS version 22 software to test: validity test, reliability test, Service Quality (SQ), Customer Satisfaction Index (CSI) and Importance Performance Analysis ( IPA). The results showed that overall service quality (SQ) has a negative gap of 0.23 which means that the services provided by Cafe Kofi Sawangan Depok are not good enough. Then for the value of the consumer satisfaction index at Cafe Kofi Sawangan Depok, currently it is found at 83.63%, which means that consumers feel quite satisfied but are not considered to be maximized overall, and in the importance performance analysis (IPA) analysis, there are no service attributes that must be considered. but the Cafe needs to improve every existing attribute in order to meet consumer desires..